The Function of Non-Formal Education Institutions in Improving Human Resources - Ramadhani, Tiara; Putri, Siska Elasta; Fadri, Zainal; Purba, Olivia Rovince (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to describe the background of the birth of the Sumatra Volunteer Foundation, analyze the function of the Sumatra Volunteer Foundation and see the impact caused by the presence of the Sumatra Volunteer Foundation as a non-formal education institution in Jorong Balai Labuah, Lima Kaum District, Tanah Datar Regency. This research uses qualitative research methods using a phenomenological approach. The instrument in this study makes the researcher the main instrument. Data were obtained through observation, interviews and document studies. The data that has been collected is analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate that the birth of the Sumatra Volunteer Foundation as a non-formal institution was motivated by the desire to improve the level of education, especially in Jorong Balai Labuah, Lima Kaum District, Tanah Datar Regency. Researchers found that there are several functions of the Sumatra Volunteer Foundation 1). Improving children's education 2). Empowering the community 3). Designing or producing products that have selling value 4). Waste Bank 5). Environmental care activities. The impact caused by the existence of the Sumatra Volunteer Foundation is, 1).┬á Character building 2). Improve the ability to speak English, 3). Concern for the environment, 4). Open insight.